A GREEN MARKETING VISION OF THE ROMANIAN COMPANIES PROMOTES A BUSINESS SUSTAINABLE DEVELOPMENT - CONSTANTINESCU, Lucreția Mariana; ȚĂNĂSESCU, Diana (Annales Universitatis Apulensis Series Oeconomica, 2014)
The sustainable product concept includes a variety of economic, social and environmental considerations. A sustainable product is an item or service that minimizes its impact on resource use and environment and maximizes that on society at each stage of its life cycle. The improvement of both characteristics must become the constant objective of the producers. The more they succeed to achieve these objectives, the more sustainable the products become. The end product of sustainable marketing consists in its contribution to the sustainable development by the favorable impact on its economic, social and environmental constituent parts (Yazdanifard and Mercy, 2011, p.638) The introduction of the environmental protection into the marketing equation to promote the consideration of the social aspect which defends the environmental interests of the society (Hopfenbech 1994, p.300) provided a major challenge for the Romanian entrepreneurs in the business area regarding to a multidimensional transformation process. This paper aims the successive steps of an organizational complete model considered by us as essential to draw the social responsible enterprise status focus to "consumer & environment" to increase their good effets upon society.